A Study of the Growth Patterns of Breast Carcinoma Using 3D Reconstruction: A Pilot Study. Issue 1 (17th November 2016) - Merrill, Andrea L.; Buckley, Julliette; Tang, Rong; Brachtel, Elena; Rai, Upahvan; Michaelson, James; Ly, Amy; Specht, Michelle C.; Yagi, Yukako; Smith, Barbara L.
Abstract: Lumpectomy with microscopically clear margins is a safe and effective approach for surgical management of breast carcinoma. Margins are positive for tumor in 18–50% of lumpectomies, as it is not possible to accurately determine the shape or microscopic borders of a tumor preoperatively or intraoperatively. We examined the 3D microanatomy and growth patterns of common breast carcinoma subtypes to provide guidance for lumpectomy surgery. Prospective consent was obtained for the use of excess tissue from patients undergoing lumpectomy or mastectomy for breast carcinoma. Tissue blocks from nine breast carcinomas were serially sectioned. Hematoxylin and eosin‐stained slides at 100 μm intervals were scanned using a Nanozoomer (Hamamatsu, Japan) microscopic‐resolution scanner. Three‐dimensional reconstructions of tumors were created from scanned images using Reconstruct, open‐access software. Breast carcinoma subtypes demonstrated characteristic growth patterns within breast tissue, which may have implications for lumpectomy surgery. Invasive ductal carcinomas showed a spherical shape, with a spiculated surface representing tumor cells infiltrating into surrounding parenchyma. Ductal carcinoma in situ appeared to spread along the duct system, creating dilated, tortuous, tumor‐filled ducts. The invasive lobular carcinomas examined had a haphazard, linear, infiltrative growth pattern, different from the shape seen in ductal carcinomas. Our preliminary work suggests that invasive ductal and invasive lobular carcinomas appear to have distinct growth patterns in three dimensions and ductal carcinoma in situ appears to grow in a linear fashion along the duct network. The microanatomy studies described have the potential to guide refinements in breast lumpectomy technique.